Mapping the Evolution of Tiered Diagnostic Instruments for Identifying Students’ Misconceptions in Physics: A Systematic Review of Indonesian Research (2015–2025) (Jurnal Pendidikan Fisika, 2025)
Misconceptions in physics education are a significant challenge, hindering students' understanding and ability to solve scientific problems.  Addressing these misconceptions is essential for enhancing learning outcomes and improving instructional methods. This study seeks to provide a comprehensive analysis of how diagnostic tests have been developed and applied to identify misconceptions in the context of physics education in Indonesia. A Systematic Literature Review methodology was used to analyze 186 scientific articles published between 2015 and 2025, indexed in Google Scholar. The research followed the PRISMA framework to ensure a transparent, replicable process. The findings indicate that diagnostic tests in Indonesia have evolved from simpler two-tier formats to more complex six-tier systems. Among these, the four-tier diagnostic test was the most commonly utilized, proving effective in identifying misconceptions by capturing students' answers, the reasoning behind those answers, and their confidence levels. The review also identified specific topics where misconceptions were most prevalent, including Particle Dynamics, Heat and Temperature, and Vibrations and Waves. These areas showed consistent patterns of misunderstanding across multiple studies. This study underscores the need for continued advancements in diagnostic tools to improve their reliability and validity. It also highlights the importance of exploring less-studied physics topics and expanding the use of multi-tier diagnostic tests. Such efforts are crucial for refining instructional strategies and improving students' conceptual learning in Indonesian physics education. The findings contribute to the field of physics education by offering actionable insights for educators and researchers in designing targeted interventions and advancing conceptual learning.